100k views
3 votes
4+3(3x + 1) = 29 - 2x

2 Answers

3 votes

Answer:

x=2

Explanation:

4 + 3(3x+1)=29 − 2x

4 + (3)(3x) + (3)(1)=29 + −2x

4 + 9x + 3=29 + −2x

9x + 7=−2x + 29

9x + 7 + 2x=−2x + 29 + 2x

11x + 7=29

11x+7 − 7=29 − 7

11x=22

11x /11=22/11

x=2

User Rogers
by
5.7k points
5 votes

Answer:

Explanation:

4 + 9x + 3 = 29 - 2x

9x + 7 = 29 - 2x

11x = 22

x = 2

User Ungeheuer
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.